IDENTIFIKASI DAN UJI AKTIVITAS SENYAWA FLAVONOID DARI EKSTRAK DAUN TREMBESI (Albizia saman (Jacq.) Merr) SEBAGAI ANTIBAKTERI Escherichia coli - Pater Suteja, I Kadek; Susanah Rita, Wiwik; Gunawan, I Wayan Gede (Jurnal Kimia (Journal of Chemistry), 2016)
Identification of flavonoid from the leaves of rain tree ( Albizia saman (Jacq.) Merr) and its antibacterial activity test against Escherichia coli (E.coli ) has been performed. This research aims to determine the type of flavonoid in rain tree leaves and its antibacterial activity against E. coli . Extraction was done by maceration and partition methods, separation was achieved by column chromatography, antibacterial activity was tested by disk diffussion method, and the identification was done by Ultraviolet-visible (UV-vis) and Infrared spectrophotometry. Extraction of 1 kg of rain tree powder with 5 L ethanol produced 73.38 g of concentrated ethanol extract. The partition process produced 26,34 g of n-hexane, 8,12 g of ethylacetate, 19,37 g n-butanol, and 12,56 g of water extracts. Phytochemical test of the extracts showed that the n-butanol extract contained flavonoids. Antibacterial activity of n-butanol extract towards E.coli showed a medium activity with a diameter inhibition of 6.3 mm. MIC value ??was 2% (w/v) with a diameter inhibition of 1 mm. Separation using column chromatography with the eluent of n-butanol: methanol: chloroform (5: 3: 2) obtained four isolates but only one isolate (isolate B with Rf 0.58) which contained flavonoids. Analysis with infrared spectroscopy showed that the isolate B contained functional groups of OH, C-OH, aliphatic CH, C = O ketones, C = C aromatic, COC ether, and aromatic CH. Analysis with UV-Vis spectrophotometer indicated that isolate B is isoflavon compound with a hydroxy groups at C-5 and C-7. The isolate was relatively pure by TLC. The isolate showed a low antibacterial activity.
Keywords: Albizia saman (Jacq.) Merr, Flavonoid, Antibacterial, Escherichia coli